Harmine Alleviated Sepsis-Induced Cardiac Dysfunction by Modulating Macrophage Polarization via the STAT/MAPK/NF-κB Pathway - Ruan, Weibin; Ji, Xinyun; Qin, Yating; Zhang, Xinxin; Wan, Xiaoning; Zhu, Chuanmeng; Lv, Chao; Hu, Chongqing; Zhou, Juan; Lu, Li; Guo, Xiaomei (Frontiers in Cell and Developmental Biology, 2022)
Sepsis is a dysregulated systemic inflammatory response that often leads to cardiac dysfunction, which is termed sepsis-induced cardiomyopathy (SIC). Harmine, a natural β-carboline alkaloid compound, has been shown to exert pharmacological effects on several diseases. Here, we investigated whether harmine protected against SIC development and the underlying mechanisms. In vitro, the expression of the M1 phenotype markers iNOS and COX-2 was increased in RAW 264.7 cells stimulated with lipopolysaccharide (LPS), but this effect was reversed by the harmine intervention. Furthermore, LPS-induced increases in the levels of inflammatory cytokines, including IL-1β, IL-6, TNF-α, iNOS, COX-2, PGE2 and TXB2, generated by macrophages were suppressed when the cells were pretreated with harmine. Meanwhile, our findings showed that harmine administration effectively attenuated inflammation and apoptosis in H9c2 cells in the proinflammatory environment produced by macrophages, as evidenced by reductions in NLRP3 and cleaved caspase 3 levels and the p-NF-κB/NF-κB ratio. The western blot results indicated that the mechanisms underlying harmine-mediated inhibition of M1 polarization might be associated with suppression of STAT1/3, NF-κB and MAPK activation. Furthermore, an LPS injection induced cardiac dysfunction and decreased the survival rate of mice, which were alleviated by harmine treatment, and the relevant mechanism was possibly attributed to a drug-induced attenuation of the inflammatory and apoptotic processes in cardiomyocytes. Collectively, these results implied that harmine treatment protected against SIC by suppressing M1 phenotypic polarization and inflammation in macrophages.